Cortisol prevents the suppressive effect of LPS on bovine oocyte maturation in vitro - Sameera PREMARATNE; Mahiro TAMURA; Omowumi ADEMOLA; Yuki MURANISHI; Masafumi TETSUKA (The Journal of Reproduction and Development)
During the periovulatory period, local production of cortisol surges in the bovine cumulus-oocyte complex (COC), although its physiological significance is not well understood. As a potent anti-inflammatory agent, cortisol may protect the COC from inflammation caused by lipopolysaccharide (LPS), an endotoxin known to cause infertility in postpartum cows. This study examined the effect of cortisol, together with progesterone (P4), on LPS-challenged bovine oocyte maturation. COCs were aspirated from follicles 2–5 mm in diameter and subjected to in vitro maturation for 21 h with various combinations of LPS, cortisol, cortisone (a substrate for cortisol production), trilostane (a P4 synthesis inhibitor), and nomegestrol acetate (NA; a synthetic progestogen). LPS (0.001, 0.01, 0.1, 1 μg/ml) suppressed oocyte maturation in a dose-dependent manner, and this effect was reversed by concomitant treatment with cortisol (0.1 μM). COCs converted cortisone to cortisol, and the locally produced cortisol (approximately 0.01 μM) was capable of negating the suppressive effect of LPS (1 μg/ml) on oocyte maturation. Trilostane suppressed oocyte maturation by eliminating P4 production, indicating the crucial role of P4 in this process. LPS equally suppressed oocyte maturation, regardless of the presence or absence of P4 or the various doses of NA (0.001–1 μM). This suggests that P4 alone does not inhibit the action of LPS. However, in the absence of P4, cortisol could not suppress the LPS effect on oocyte maturation. Collectively, these findings suggest that the bovine COC can protect itself from the suppressive effects of LPS by producing cortisol, with P4 being essential for this function.